The relationship between leadership and internal customer satisfaction within a motor manufacturing company in Gauteng - Samuel, Glen (Rhodes University, Faculty of Commerce, Investec Business School, 2005)
This research investigates the relationship between leadership and internal customer satisfaction, also called employee satisfaction in this document. The research is conducted within an automotive manufacturer situated in the province of Gauteng, South Africa. The Service Profit Chain forms the foundation on which this research is based as it suggests that the various factors within the service delivery system of an organisation ultimately affect the success of an organisation. From the Service Profit Chain, it is established that a factor that affects employee satisfaction is the leadership within the organisation. The Full Range Leadership Development Theory provides the backbone for analysing the leadership style of each manager by using the Multifactor Leadership Questionnaire. The company's employee satisfaction model provides the theoretical construct against which the employee satisfaction of the managers' subordinates is measured using the company's employee satisfaction questionnaire. Information was gathered from the managers who rated their leadership styles as they perceived it; and from their respective subordinates who rated the managers' leadership style as they perceived it and also their satisfaction as employees as they perceived it. Data obtained from each instrument, for the respective managers, was then statistically analysed. The reliability of the data could not be proved for some of the factors of the 2 research instruments. However, this research found a statistically significant relationship between transformational leadership and some factors of employee satisfaction, albeit a weak relationship. The null hypothesis was rejected and the alternate hypothesis accepted. A statistically significant relationship exists between leadership style and employee satisfaction levels within an automotive manufacturing organisation.
Keywords: Automobile industry and trade -- Employees -- South Africa -- Gauteng; Automobile industry and trade -- Customer services -- South Africa -- Gauteng; Job satisfaction; Customer services -- Management; Industrial relations -- South Africa -- Gauteng; Employee morale; Personnel management